1991
DOI: 10.1029/91jb01837
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of low P wave velocity structures in the subducting plate of the central New Hebrides, southwest Pacific

Abstract: Arrival times of compressional (P) and shear (S) waves generated by earthquakes located in the New Hebrides subduction zone and recorded by local and regional arrays of seismographs are used to determine large-scale one-and three-dimensional elastic wave velocity structures of the subduction zone between 15 ø and 20øS and from the surface to about 250 km depth. The results obtained from inverting the locally and regionally recorded arrival times individually corroborate each other, and they are inverted jointl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…The inversion method utilized in this study has been successfully applied before in a variety of tectonic environments (e.g. Thurber 1983Thurber , 1984Abers & Roecker 1991;Ni, Ibenbrahim & Roecker 1991;Prevot et al 1991).…”
Section: Discussion a N D Conclusionmentioning
confidence: 99%
“…The inversion method utilized in this study has been successfully applied before in a variety of tectonic environments (e.g. Thurber 1983Thurber , 1984Abers & Roecker 1991;Ni, Ibenbrahim & Roecker 1991;Prevot et al 1991).…”
Section: Discussion a N D Conclusionmentioning
confidence: 99%
“…Louat et al (1988) suggested, on the basis of earthquake foci in the central NHIA, that the subducted slab may be broken and have a seismic gap from -50-150 km depth. Prevot et al (1991) suggest that this seismic gap represents a thermal anomaly of some 750°C, which alters the physical properties of the subducted slab beneath this region. In this region, the top of the slab is about 150-200 km beneath the arc volcanoes.…”
Section: Location Of the Enriched Sourcementioning
confidence: 99%
“…Seismological studies also indicate a mean forearc plate crustal thickness of 25–30 km (Baillard et al, ; Coudert et al, ; Prevot et al, ). Prevot et al () showed evidence that the Moho was locally shallower beneath south Santo and deeper beneath Malekula.…”
Section: Geological and Local Seismological Overviewmentioning
confidence: 99%
“…Seismological studies in the region have used global data, a 1978-1988 network of 27 land stations deployed over the island arc (e.g., Coudert et al, 1984;Prevot et al, 1991) and the 2008-2009 ARC-VANUATU local forearc seismology network (Baillard et al, 2015). These studies indicate that the probable prolongation of the DFZ beneath Vanuatu correlates with a locally shallow subduction interface (Baillard et al, 2015) and, at 100-250-km depth, with alignments in seismicity and a region of high P wave attenuation (Baillard et al, 2018;Chung & Kanamori, 1978;Marthelot et al, 1985;Pascal et al, 1978).…”
Section: Geological and Local Seismological Overviewmentioning
confidence: 99%